The Proposal of Virtual Reality Model for Hotel Front Office Employees Training - Stepan CHALUPA; Martin KOTEK; Jan HUSAK; Jakub STEJSKAL; Michal KOTEK; Martina PERUTKOVA; Jirina JENCKOVA; Martin KOCOUREK (Communications of International Proceedings, 2021)
This article aims to propose the model of hotel front office for virtual reality-based training as a platform for the development of the hotel employees' soft skills, stress management and advanced customer care. Due to CoVid-19 pandemics, the hoteliers are struggling to keep up with the employers in other service-oriented industries that propose higher salaries and more workspace stability to former hotel employees. Due to the lack of employees and changes in the labor market, hoteliers need to find sophisticated employee training and requalification approaches. The new employees are commonly hired from other industries with a lower proportion of employee to customer interactions. This article proposes the training environment for soft skills development and the methodology for such a training program. Photogrammetry was used to create the realistic model of the hotel front office, and the avatars were made using the Virtual Capture and post-production in 3D Studio Max. Using this approach, trainees can train their communication skills and directly see the mimics and the changes in non-verbal communication, improving their empathy and observation skills. The educational institutions and professional associations can implement this model, and individual businesses to support their operations and reduce the time needed to prepare the new employees while onboarding.
Keywords: Virtual reality; soft skills training; photogrammetry; eye-tracking.